Cash Holdings, Capital Structure, and Financing Risk - Sun, Qi; Xia, Junjie (Journal of Financial and Quantitative Analysis, 2022)
Abstract This article quantifies a new motive of holding cash through the channel of financing risk. We show that if access to future credit is risky, firms may issue long-term debt now and save funds in cash to secure the current credit capacity for the future. We structurally estimate the model and find that this motive explains approximately 24% to 30% of cash holdings in the data. Counterfactual experiments indicate that the value of holding cash is approximately 8% of shareholder value.